One of a set of charts prepared by Capt Cook previously to his Expedition to contain all previous discoveries from the collection of drawings purchased by Henry Ward Pool, 1856. - Cook, James, 1728-1779 (1779)
Manuscript map. Title handwritten in upper left. Grayscale;